An optimized xylene-free protein extraction method adapted to formalin-fixed paraffin embedded tissue sections for western blot analysis - Mansour, Anthony G. (2017)
Deparaffinization of formalin-fixed paraffin embedded (FFPE) tissues with xylene currently remains a major challenge to the biomedical community. We developed an efficient xylene-free protocol to isolate proteins from archived FFPE human tissue sections. A total of 79 different types of FFPE tissue sections of 8 µm thickness were obtained from various archived FFPE specimens. Deparaffinization was conducted by gently washing each section with around 1 ml of hot distilled water (≈80°C). The deparaffinized tissues were homogenized in lysis buffer, and the isolated proteins were quantified and efficiently resolved using western blot analysis for the presence of Protein kinase B (PKB/AKT) and β-actin. Moreover, a significant amount of proteins was successfully isolated with an average of 2.31 µg/µl. The migration pattern of AKT and β-actin obtained from the specimens was similar to the positive control obtained from protein lysates prepared from in vitro cultured MDA231 cancer cell lines. AKT was successfully identified in all specimens, and β-actin protein was resolved with an efficiency higher than 80%. The entire extraction procedure requires only 20 minutes. This newly developed technique is an efficient, safe, cost-effective, and rapid method to isolate proteins from FFPE tissue sections adequate for molecular analysis.